2015
DOI: 10.2337/dc14-1840
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Mortality Risk After Hyperglycemic Crisis Episodes in Geriatric Patients With Diabetes: A National Population-Based Cohort Study

Abstract: OBJECTIVEHyperglycemic crisis is one of the most serious diabetes-related complications. The increase in the prevalence of diabetes in the geriatric population leads to a large disease burden, but previous studies of geriatric hyperglycemic crisis were focused on acute hyperglycemic crisis episode (HCE). This study aimed to delineate the long-term mortality risk after HCE. RESEARCH DESIGN AND METHODSThis retrospective national population-based cohort study reviewed, in Taiwan's National Health Insurance Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 19 publications
0
37
0
1
Order By: Relevance
“…The major difference of long-term mortality after HCE between non-elderly and elderly was that HCE significantly increases the subsequent mortality risk even more than 8 years in the non-elderly but limited to B6 years in the elderly [15]. The elderly have more comorbidites which may dilute the HCE effect on the long-term mortality after 6 years.…”
Section: Risk Factors For All-cause Mortality In Dm Patientsmentioning
confidence: 98%
See 1 more Smart Citation
“…The major difference of long-term mortality after HCE between non-elderly and elderly was that HCE significantly increases the subsequent mortality risk even more than 8 years in the non-elderly but limited to B6 years in the elderly [15]. The elderly have more comorbidites which may dilute the HCE effect on the long-term mortality after 6 years.…”
Section: Risk Factors For All-cause Mortality In Dm Patientsmentioning
confidence: 98%
“…The long-term effect of uncontrolled diabetes contributes to various complications, including death [1]. A study showed that geriatric patients (C65 years) with diabetes had a higher mortality risk after HCE during the first 6 years of follow-up [15]. However, the subsequent mortality of the non-elderly (\65 years) after HCE has never been clarified.…”
Section: Introductionmentioning
confidence: 98%
“…Long-term mortality after hyperglycemic crises are significantly higher in older adults (23). In the Perspective by Korytkowski and Forman (24), the authors point out that although older adults are at higher risk of atherosclerotic cardiovascular disease, most of the studies examining the benefits for aggressive glucose-lowering and cardiovascular risk factor modification (i.e., lipid-lowering, hypertension, and antiplatelet therapies) are in nonelderly adults.…”
mentioning
confidence: 99%
“…Diabetes with poor compliance was defined as a hospitalization with the diagnosis of a hyperglycemic crisis episode (HCE) (ICD-9-CM codes: diabetic ketoacidosis, 250.1 or hyperosmolar hyperglycemic state, 250.2). 24 The index date for each diabetic patient was the date of his or her first diabetes diagnosis. The index date for subjects in the unexposed group was set as January 1,2005.…”
Section: Analysis Of the Association Between Diabetes And Risk Of Acumentioning
confidence: 99%
“…4,23,38,39 Second, laboratory findings relevant to the severity of diabetes, including HbA1c and blood glucose values, were unavailable in the database. Alternatively, since uncontrolled diabetes is the most common factor precipitating HCE, 24 diabetes with poor compliance was defined as diabetes with at least one episode of HCE. Because diabetic ketoacidosis and the hyperosmolar hyperglycemic state are extremely severe states, they may not serve as perfect substitutes for poor control.…”
Section: Limitationsmentioning
confidence: 99%